2017
DOI: 10.1152/ajpheart.00216.2017
|View full text |Cite
|
Sign up to set email alerts
|

A-type K+ channels contribute to the prorenin increase of firing activity in hypothalamic vasopressin neurosecretory neurons

Abstract: Recent studies have supported an important contribution of prorenin (PR) and its receptor (PRR) to the regulation of hypothalamic, sympathetic, and neurosecretory outflows to the cardiovascular system, including systemic release of vasopressin (VP), both under physiological and cardiovascular disease conditions. Still, the identification of precise cellular mechanisms and neuronal/molecular targets remain unknown. We have recently shown that PRR is expressed in VP neurons and that their activation increases ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
(92 reference statements)
2
8
0
Order By: Relevance
“…While the latter decreases tonic firing frequencies, the total number of APs elicited by a given depolarizing pulse is increased, thus demonstrating the limitation of AP firing by I A . This view is corroborated by findings from different neuronal cell types where receptor stimulation-dependent activation and inhibition of I A reduces and increases the rate of firing APs, respectively (Kloppenburg et al 1999 ; Pitra and Stern 2017 ). In a similar way the knock down of Kv4.1 channels increased neuronal firing rates (Hermanstyne et al 2017 ).…”
Section: Discussionmentioning
confidence: 57%
“…While the latter decreases tonic firing frequencies, the total number of APs elicited by a given depolarizing pulse is increased, thus demonstrating the limitation of AP firing by I A . This view is corroborated by findings from different neuronal cell types where receptor stimulation-dependent activation and inhibition of I A reduces and increases the rate of firing APs, respectively (Kloppenburg et al 1999 ; Pitra and Stern 2017 ). In a similar way the knock down of Kv4.1 channels increased neuronal firing rates (Hermanstyne et al 2017 ).…”
Section: Discussionmentioning
confidence: 57%
“…Thus, it is reasonable to speculate that the PRR-mediated increase of VP levels in DOCA-salt hypertension involved changes in MNN membrane excitability and/or firing activity. We recently reported that PRR receptors are densely expressed both in VP and oxytocin MNNs and that their activation evokes an excitatory effect, leading to an increase in their firing activity (41,42). These effects were ANG II independent, requiring an increase in intracellular Ca 2ϩ levels (41), as well as an inhibition of the I A (42).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that PRR receptors are densely expressed both in VP and oxytocin MNNs and that their activation evokes an excitatory effect, leading to an increase in their firing activity (41,42). These effects were ANG II independent, requiring an increase in intracellular Ca 2ϩ levels (41), as well as an inhibition of the I A (42). The later effect involved an increased rate of I A inactivation and a shift in the steady-state voltage-dependent inactivation function toward more hyperpolarized membrane potentials (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations